2021
DOI: 10.1111/den.14006
|View full text |Cite
|
Sign up to set email alerts
|

Possible reasons for the regrettable results of patency of an inside stent in endoscopic transpapillary biliary stenting

Abstract: Endoscopic biliary decompression is a minimally invasive procedure for cholestasis since the first endoscopic retrograde cholangiopancreatography-guided biliary stenting performed by Soehendra and Reynders-Frederix. Among the endoscopic biliary decompression, endoscopic transpapillary biliary stenting (EBS), is a mainstream choice and presently has two methods of placement: stenting above the sphincter of Oddi (SO) (suprapapillary) and stenting across the SO (transpapillary). Stent patency is the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
(106 reference statements)
0
14
1
Order By: Relevance
“…Although stent placement across the papilla has been the standard of care, the concept of metal and plastic stents above the papilla has been investigated both in malignant and benign biliary strictures [9]. However, most studies were retrospective with a small sample size, and no RCTs have proven the superiority of stents above the stricture to stents across the papilla thus far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although stent placement across the papilla has been the standard of care, the concept of metal and plastic stents above the papilla has been investigated both in malignant and benign biliary strictures [9]. However, most studies were retrospective with a small sample size, and no RCTs have proven the superiority of stents above the stricture to stents across the papilla thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of anti-reflux biliary stents have been conducted, but their role is still controversial [8]. Stents above the papilla, so-called "inside stents," have been investigated using both metal and plastic stents [9]. Fully-covered self-expandable metal stents (FCSEMS) with a retrieval lasso are increasingly utilized for benign biliary strictures at the hilum or anastomotic strictures [10][11][12][13], but FCSEMS is not always indicated in patients with nondilated ducts.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial 86 has also reported that efficacy of bilateral SIS and SBS deployment may be similar in terms of total adverse events, technical and clinical success, stent patency, and survival (the stent patency rates at 3 and 6 months was higher in the SIS group without statistical difference). Furthermore, it has been recommended that SEMS (via SBS deployment) should be placed above the papilla to avoid pancreatitis and methods involving stent placement across the papilla should be avoided 87,88 . Exchangeable IS and slim‐covered SEMS (6 mm in diameter) have been used for not only preoperative drainage but also unresectable PHCC 89–92 .…”
Section: Drainagementioning
confidence: 99%
“…Furthermore, it has been recommended that SEMS (via SBS deployment) should be placed above the papilla to avoid pancreatitis and methods involving stent placement across the papilla should be avoided. 87,88 Exchangeable IS and slim-covered SEMS (6 mm in diameter) have been used for not only preoperative drainage but also unresectable PHCC. [89][90][91][92] Furthermore, EUS-guided biliary drainage (EUS-BD) has recently been reported for unresectable PHCC [93][94][95] with a technical success rate of over 90% and a clinical success rate of over 70%.…”
Section: Drainage For Unresectable Casesmentioning
confidence: 99%
“…A previous study has shown that placement of the stent above the intact sphincter of Oddi is associated with longer stent patency and lower occlusion rate. 4 In hilar MBO, stent patency is affected by various factors such as insertion method (side-by-side, stent-in-stent) and how much intrahepatic bile duct drainage has been performed. Thus, there is a limit to the interpretation of the role of stent position with AOV.…”
Section: Introductionmentioning
confidence: 99%